HADIS: DARI ITBA’ AL-SUNNAH HINGGA INKAR AL-SUNNAH - Nuraini Habibah (IAINU Kebumen Prodi IAT, 2025)
Hadith is the second source of Islamic teachings after the Qur'an. Throughout history, Muslims have had various approaches to understanding and practicing hadith. Some understand hadith as a valid and correct legal basis for human life, because it originates from the Prophet Muhammad (peace be upon him). Others deny or reject it because its veracity is considered uncertain and because they believe that everything is explained in the Qur'an, thus requiring no other source. This article will explore how hadith were understood and practiced by early Muslims, and how differences of opinion and interpretation have influenced their understanding of hadith.